Somatic embryogenesis of Sandalwood (Santalum album L.) - Toni Herawan; Mohammad Na'iem; Sapto Indrioko; Ari Indrianto (Indonesian Journal of Biotechnology, 2014)
Sandalwood (Santalum album L.) is native species of Indonesia, especially in East Nusa Tenggara, is oneof the twenty two species of the genus Santalum in the world. Sandalwood is an important tree because it hashigh economic value can produce sandal oil these can be used for perfumes, cosmetics, pharmaceuticals, andare often used in religious ceremonies. In vitro particularly somatic embryogenesis has been widely appliedin the propagation of sandalwood. The Objective of this research is to obtain regeneration of sandalwoodthrough somatic embryogenesis using leaves explant from various clones. Medium for embryo induction is MS(Murashige and Skoog, 1962) solid medium containing treatment of 2,4-D (2,4-Dichlorophenoxyacetic acid)at various concentrations. To the media 0,15 mg /l kinetin, 40 g/l sucrose, and 2,5 g/l gelrite were added.Culture were incubated in the dark. Medium for Embryo development (maturation) is MS solid mediumcontaining treatment of BAP (Benzyl-amino-purine) at various concentrations. To the media 0,01 mg /l NAA(Napthalene-acetic-acid), 40 g/l sucrose, and 2,5 g/l gelrite were added. Culture were incubated in the light. Tostudy the specifi c structure of sandalwood somatic embryo early detection was conducted using histologicalanalysis. Results of anova showed that the clones, media, and interaction between clones with media did notsignifi cantly affect the development of sandalwood callus percentage. Results of anova showed that the clonesand BAP concentration signifi cantly effect to the embryo development of sandalwood.